Work and labor in the digital age - P. Vallas, Steven; Kovalainen, Anne (Research in the sociology of work ;, 2019)
This volume presents the most recent studies of work and labor in the digital age as it unfolds in both Europe and the United States.One of the critical questions facing modernity concerns the reconfiguration of paid employment, which has been subject to wholesale changes that have widespread consequences for workers, their families, and the institutional structure that characterizes capitalist societies. A key driver of these changes has been the digital revolution and the rapid proliferation of the gig economy. Together with social network sites for hiring, the spread of robotics, and the rise of artificial intelligence and machine learning, they leave virtually no occupation untouched. - Resumé vydavatel